2020
DOI: 10.1155/2020/9367916
|View full text |Cite
|
Sign up to set email alerts
|

Study on Deformation Mechanism and Support Measures of Soft Surrounding Rock in Muzhailing Deep Tunnel

Abstract: The deformation of Muzhailing deep tunnel is about 2.3 m in the process of construction, which is difficult to be controlled by the traditional “anchor-grouting integration” support system. This paper deeply analyzes the geological characteristics, rock mechanics characteristics, and surrounding rock failure characteristics of Muzhailing tunnel. The deformation mechanism and the failure of the support system are analyzed through the numerical simulation, theoretical analysis, and field test. The authors propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Aksoy et al [14] adopted a non-deformable support scheme for the large deformation tunnel. Tao et al [15] found that the deformation of the Muzhailing tunnel was due to the plastic flow and swelling deformation of the surrounding rocks. In a case study, Wang et al [16] studied and optimized the construction scheme and supporting technology for the high stress and jointed soft rock tunnel.…”
Section: State Of the Artmentioning
confidence: 99%
“…Aksoy et al [14] adopted a non-deformable support scheme for the large deformation tunnel. Tao et al [15] found that the deformation of the Muzhailing tunnel was due to the plastic flow and swelling deformation of the surrounding rocks. In a case study, Wang et al [16] studied and optimized the construction scheme and supporting technology for the high stress and jointed soft rock tunnel.…”
Section: State Of the Artmentioning
confidence: 99%
“…At present, the main mining countries have entered into the deep mining stage and initiated for developing deep roadway support which normally faces challenges in deep mining [1,2]. It is difficult to ensure the stability of the deep broken soft rock roadway due to several influencing factors such as mining activities, rock mass physical and mechanical properties, and high-stress field, which directly cause difficulties in finding the stability control of surrounding rock [3][4][5][6][7][8][9][10][11]. e abundant scientific research achievements have been done by many researchers around the world to solve the ground support problem of deep soft surrounding rock roadway through developing new technology for deep soft rock roadway surrounding rock control, new theory, and performing the industrial test.…”
Section: Introductionmentioning
confidence: 99%
“…ey compared the numerical simulation with the field test data and concluded that the NPR anchor support significantly reduced the asymmetric deformation of the tunnel surrounding rock, and the deformation of the surrounding rock was smaller than that of the steel arch support. Tao et al [28] proposed an improved "NPR cable + steel arch frame + concrete" support mode. Yang et al [29] proposed a support scheme for deep-buried soft rock roadways, namely, a new "bolt-cable-mesh-shotcrete + shell" combined support.…”
Section: Introductionmentioning
confidence: 99%